SOME ASSOCIATED FACTOR RELATED TO KNOWLEDGE, ATTITUDE AND PRACTICES ON DENGUE PREVENTION IN DONG XUYEN WARD, LONG XUYEN CITY, AN GIANG PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: To describe some associated factors related to knowledge, attitude, and practices ofpeople in Dong Xuyen ward, Long Xuyen city, An Giang province in 2021.Methods: A cross-sectional study was conducted with a sample size of 350 people from 18/02/2021to 30/03/2021.Results: The study found the relationship between occupational factors, number of family membersand knowledge, attitude, and practice about dengue fever prevention. Respondents who have correctknowledge were 16,307 times more likely to have good practice than those with incorrect knowledge(95% CI: 9,296-28,606). Respondents who have good attitude were 4,889 times more likely to havecorrect practice than those with poor attitude (95% CI: 3,077-7,767).
Keywords: Dengue fever, knowledge, attitude, practice, Dong Xuyen, Long Xuyen, An Giang.